Evaluasi Keandalan Catatan Akuntansi Persediaan dalam Pelaksanaan Pengendalian Intern (Studi Kasus Pada CV Juberta di Kasui, Way Kanan) - Iskandar Ali Alam; Krukas Pari; Syamsu Rizal (Universitas Bandar Lampung (UBL), 2010)
The purpose of this study was to determine whether inventory records in the implementation of internal control has been reliably. Authors proposed hypothesis is: